Principles of Together and Family As the Basis of Development Indonesian Economic Law - Elli Ruslina (Budapest International Research and Critics University, 2022)
This study begins with the findings in the legislation in the field of economic law, that the principle of mutualism and kinship listed in Article 33 of the 1945 Constitution has not been realized substantially in its articles, but only stated in the preamble. In the substance of the article even leads to the principle of capitalistic / liberalistic which prioritizes the interests of individuals or groups. The purpose of the study of the basic model of unity and family in the development of Indonesian economic law, is to find and redefine the fundamental values of togetherness and family as contained in Article 33 of the 1945 Constitution as defined by the pounding fathers of the nation, as constitutional mandates. In addition, the aim is to be understood by related parties that the principle of mutualism and kinship is important because it contains concepts or principles that prioritize the interests of many people (the sovereign-people). The research approach method is normative juridical by reviewing secondary data in the form of legislation and literature, supported by primary data through observation and interviews with related parties. This research is in line with the Strategic Plan of Pasundan University with a vision and mission, among others, to develop culture, including containing cultural values of mutual cooperation, togetherness, and kinship. The targeted output consists of mandatory outputs in the form of the principle of togetherness and kinship, while additional outputs in the form of journals and textbooks.